Evidence of Jet‐Scale Overturning Ocean Circulations in Argo Float Trajectories. Issue 21 (11th November 2018) - Li, Qian; Lee, Sukyoung; Mazloff, Matthew
Abstract: In a recent study, it was proposed that Reynolds stress by oceanic mesoscale eddies not only drives jets such as Subantarctic Front but also can force overturning circulations that are composed of rising motion on the poleward flank and sinking motion on the equatorward flank of the jets. In that study, the thermally indirect, jet‐scale overturning circulations (JSOCs) were detected in an eddy‐resolving model simulation of the Southern Ocean. Here observational evidence of the existence of JSOCs is demonstrated by showing that the Argo floats tend to drift poleward across the jet with the maximum drift speed coinciding with the corresponding jet maximum. This finding has an implication for the observed deep mixed layer because it was previously shown that in the model the JSOCs play a key role in preconditioning the formation of a deep and narrow mixed layer at just ~1° north of the Subantarctic Front. Plain Language Summary: In the Southern Ocean, some of the deepest mixed layers from early to late winter have a meridional scale of only ~2° and a depth of over 500 m. These mixed layers are thought to be a critical pathway for ocean ventilation of greenhouse gases and heat and thus considered as an important regulator of climate. Yet the mechanism for the key observed features of deep mixed layers is not well understood and is a subject of active research. This paper demonstrates observational evidence of an overturning circulation, which was theorized to exist and to help account for the observed feature of the deep mixed layer. Numerous efforts to understand the mechanism of the deep mixed layer are underway. Therefore, it is important to present this newly identified overturning circulation to the community in a timely manner. Key Points: From early to late winter, observed deep mixed layers in the Southern Ocean have a filamented meridional scale of only ~2° Jet‐scale overturning circulations, previously diagnosed in a model, account for the formation of the model's filamented mixed layers Argo float trajectory analysis shows that the theoretical jet‐scale overturning circulations exist in nature